2016
DOI: 10.1186/s12906-016-1032-1
|View full text |Cite
|
Sign up to set email alerts
|

Allium hookeri root protects oxidative stress-induced inflammatory responses and β-cell damage in pancreas of streptozotocin-induced diabetic rats

Abstract: BackgroundWater extract from the root of Allium hookeri (AH) shows anti-inflammatory, antioxidant, and free radical scavenging effects. In this study, the ameliorating effects of AH on oxidative stress-induced inflammatory response and β-cell damage in the pancreas of streptozotocin (STZ)-induced type 1 diabetic rats were investigated.MethodsAH (100 mg/kg body weight/day) was orally administered every day for 2 weeks to STZ-induced diabetic rats. After the final administration of AH, biochemical parameters inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 46 publications
5
32
0
Order By: Relevance
“…In our study, serum insulin levels were significantly lower in the diabetic rats compared to the healthy Control group and the treatment groups, likely due to the destruction of pancreatic beta-cells in the STZ-induced diabetic rats. 47,50 In accordance with the literature, PTS treatment increased serum insulin levels in a dose-dependent manner. PTS may increase insulin sensitivity and increase hepatic hexokinase activity in glycolysis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, serum insulin levels were significantly lower in the diabetic rats compared to the healthy Control group and the treatment groups, likely due to the destruction of pancreatic beta-cells in the STZ-induced diabetic rats. 47,50 In accordance with the literature, PTS treatment increased serum insulin levels in a dose-dependent manner. PTS may increase insulin sensitivity and increase hepatic hexokinase activity in glycolysis.…”
Section: Discussionsupporting
confidence: 89%
“…The animal model for STZ-induced DM is characterized by elevated blood sugar levels, decreased serum insulin levels, and increased weight loss. 47 Our study showed increased weight loss in untreated diabetic rats and decreased weight loss in the diabetic rats that received PTS treatment. Compared to the other doses, 40 mg/kg/day of PTS was associated with the least amount of weight loss.…”
Section: Discussionsupporting
confidence: 47%
“…Allium hookeri has been consumed as medicinal food and contains a lot of rutin as an active ingredient. It is known to various biological properties such as antioxidant, antiobesity, antimicrobial, anti-inflammatory, and antiallergic effects [7][8][9][10][11][12]. Rutin, a quercetin-3-rhamnosylglucoside, has anti-inflammatory, antitumor, antiallergic, and vasoactive properties [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes (T1DM), the chronic autoimmune disease, results from the destruction of the in-sulin producing beta (β) cells of the pancreas, leading to a gradual decrease in β-cell mass. Accordingly, this type of diabetes shows absolute insulin deficiency and excessive glucose production (3).…”
Section: Introductionmentioning
confidence: 99%